Design of Obstacle Avoiding Robot - R., Jeyagopi (INTI International University, 2020)
In today’s world, robotics is fast growing and already interacting in many aspects of our daily lives. Robotics is part of communication advancement of technology; engineers have decided to work in this field to design or build robots which will make human life more advanced. There are various types of mobile robotics in today’s technology world. There are tracks robot, humanoid robot, water-based robot, wheels robot and etc. Thus, obstacle avoiding robot is designed using three wheels in this research. The system is implemented using Arduino platform, android application and ultrasonic sensors. This robot has been developed with the interaction of Android-based device. Arduino Uno is used as the brain of the robot. It also includes the part of the software that utilizes a portable application. In this paper, obstacle avoiding robot is designed to allow the robot itself to navigate in unknown environment by avoiding obstacles using three wheels. The proposed design is compared with the four wheels in term of movement and turning. The outcomes show that the proposed design three wheels is able to provide a steady and faster movement and turning.